Integrasi Nilai Sosial dan Akhlakul Karimah melalui Manajemen Pendidikan Islam di MI The Noor Mojokerto - Masrur Huda; Wahyu Syafa'at; Faiqotul Futhnah; Salsa Alimatul Fathiya (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2025)
This study aims to analyze the implementation of Islamic education management at MI The Noor Mojokerto in integrating social values and akhlakul karimah into the learning environment. The study utilized a qualitative method with a case study approach, where data were collected through in-depth interviews, direct observation, and document analysis. The analytical techniques involved thematic processes to identify key patterns in the strategies of Islamic education management. The findings reveal that value-based management at MI The Noor includes structured program planning, learning activities that foster the internalization of social values like mutual respect, and periodic evaluations to ensure the successful development of character based on akhlakul karimah. The conclusion of this study is that the comprehensive application of Islamic education management not only creates a conducive learning environment but also encourages students to develop religiously, socially, and academically. This study contributes to understanding the importance of integrating social values and akhlakul karimah into Islamic education management.